Pengujian Mekanik dan Biodegradabilitas Plastik Biodegradable Berbahan Baku Pati Bonggol Pisang dengan Penambahan Kitosan, Sorbitol, dan Minyak Kayu Manis - Dewi Oetary; Syaubari Syaubari; Medyan Riza (Jurnal Serambi Engineering, 2019)
Biodegradable plastic is an alternative to conventional plastic which has been very difficult to degrade and causes environmental pollution. Biodegradable plastic raw materials come from plants or plant wastes, so they are easily degraded by the environment and the utilization of waste becomes more efficient. The general objective of this study is to obtain the characteristics of plastics that meet the standards by varying the concentration of the materials used. This study used Kepok banana hump starch with variations in the concentration of chitosan, sorbitol, and cinnamon oil. The variable used is the ratio of weight of starch and water (1: 5). The concentration of chitosan nanoparticles was 0.25%, 0.5%, and 0.75%, sorbitol concentrations were 2 ml, 4 ml, and 6 ml, and the concentration of cinnamon was 0%, 0.5%, and 1%. Tests carried out are tensile strength, elongation of break, water absorption, and biodegradability. The best tensile strength results are 19.6 MPa, the best elongation is 47.69%, the highest water absorption is 53.77% and the lowest is 22.63%, and the complete degradation takes the longest time of 77 days.